2014
DOI: 10.1159/000440678
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and Etoposide in Heavily Pretreated Patients with Progressive High-Grade Glioma

Abstract: Background: Treatment of recurrent anaplastic glioma and glioblastoma remains a particular challenge in neurooncology. The lack of controlled trials results in poor evidence for all therapeutic options. Upon recurrence, many patients are treated with bevacizumab or one of the frequently used nitrosoureas such as lomustine. However, patients who still present in overall good condition after failure of multiple lines of therapy may ask for additional therapy. Methods: Here, we report our experience with the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In this study, the efficacy of CE regimen in recurrent GBM was poor which was consistent with previous report (11). However, the efficacy of CE regime was better in patients with recurrent glioma of grade 2 or 3 compared with recurrent GBM.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the efficacy of CE regimen in recurrent GBM was poor which was consistent with previous report (11). However, the efficacy of CE regime was better in patients with recurrent glioma of grade 2 or 3 compared with recurrent GBM.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, CR was observed in 1 patient with grade 2 tumor after 2 cycles of CE chemotherapy, suggesting that salvage CE regimen may be effective for patients with grade 2 recurrent gliomas. Nonetheless, the preliminary results in this study suggested that CE regimen may confer a superior clinical benefit in patients with grade 2-3 tumors compared to patients with grade 4 tumors following disease progress or recurrence after initial surgery and adjuvant therapy Since CE regimen has been widely used in different malignant tumors for decades and the reported related adverse events is similar in different diseases (11,13,25), toxicity was not a primary endpoint in this study. However, hematological toxicity was the most common adverse event observed in this study cohort and most patients received granulocyte-colony stimulating factor (GSF) treatment during the course of chemotherapy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There were 8 studies eligible which examined the use of systemic chemotherapy other than TMZ or nitrosureas for the treatment of pGBM eligible and were included in this analysis. These studies summarized in Table 3 provided Class III evidence [27][28][29][30][31][32][33][34][35].…”
Section: Q2-synthesismentioning
confidence: 99%
“…Tonder et al [33] conducted a retrospective review of 12 heavily pretreated recurrent high grade glioma patients including 8 glioblastoma patients treated with carboplatin (240mg/m2 on day 1) and etoposide (100mg/m2 on days 2 and 3) every 4 weeks. Signi cant toxicity was observed with grade 3-4 hematologic toxicity in 67% of patients.…”
Section: Platinum Compoundsmentioning
confidence: 99%